Genomic characterization of a reemerging Chikungunya outbreak in Kedougou, Southeastern Senegal, 2023 - Idrissa Dieng; Bacary Djilocalisse Sadio; Alioune Gaye; Samba Niang Sagne; Marie Henriette Dior Ndione; Mouhamed Kane; Mamadou Korka Diallo; Bocar Sow; Safietou Sankhe; Ousseynou Sene; Amadou Diallo; Madeleine Dieng; et al. (Emerging Microbes and Infections)
Chikungunya virus has caused millions of cases worldwide over the past 20 years, with recent outbreaks in Kedougou region in the southeastern Senegal, West Africa. Genomic characterization highlights that an ongoing epidemic in Kedougou in 2023 is not due to an introduction event but caused by the re-emergence of an endemic strain evolving linearly in a sylvatic context.